Association between anti-HBc positivity and hepatocellular carcinoma in HBsAg-negative subjects with chronic liver disease: A meta-analysis. Issue 30 (July 2016) - Coppola, Nicola; Onorato, Lorenzo; Sagnelli, Caterina; Sagnelli, Evangelista; Angelillo, Italo F.
Abstract : Abstract: A meta-analysis was performed to ascertain to what extent hepatitis B surface antigen (HBsAg)-negative/anti-hepatitis B core (anti-HBc)-positive subjects with chronic liver disease are at a higher risk of developing hepatocellular carcinoma (HCC) than the anti-HBc-negative. All studies included had to fulfill the following characteristics and inclusion criteria: they investigated the relationship between HBsAg-negative/anti-HBc-positive serology and the occurrence of HCC, whether a case–control or cohort study, they provided relative risk (RR) or odds ratios (ORs) and 95% confidence intervals (CIs), were available as a full text written in English, and were published and indexed up to April 2015. Twenty-six original studies met the inclusion criteria, allowing a meta-analysis on 44, 553 patients. The risk of HCC among the 9986 anti-HBc-positive subjects was 67% higher than in the 34, 567 anti-HBc-negative (95% CI = 1.44–1.95, P  < 0.0001). The results were similar when groups of patients with a different stage of liver disease (patients with chronic liver disease, patients with cirrhosis), with different ethnicity (Asian and non-Asian) and etiology (HCV and non-HCV) were considered. The risk of HCC was significantly higher in the 651 anti-HBs/anti-HBc-positive patients (RR = 1.36; 95% CI = 1.17–1.58, P  = 0.03) and in the 595 anti-HBs-negative/anti-HBc-positive subjects (RR = 2.15; 95% CI = 1.58–2.92, P  < 0.0001) than in the 1242 anti-HBs/anti-HBc negative. However, the RR from 8 studies indicated that the risk of HCC was 35% lower among the anti-HBs/anti-HBc-positive subjects compared to the anti-HBs-negative/anti-HBc-positive (RR = 0.65; 95% CI = 0.52–0.8, P  < 0.0001). This meta-analysis shows that in HBsAg-negative subjects with chronic liver disease, anti-HBc positivity is strongly associated with the presence of HCC, an association observed in all subgroups according to the stage of the disease, etiology, and ethnicity.